ANALISIS PELAKSANAAN STRATEGI POSITIONING PADA PRODUK TOYOTA AVANZA (Kasus Penjualan Toyota Avanza Pada PT. Agung Automall Pekanbaru) - Rinaldi, Oki; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. Agung Automall Sutomo Pekanbaru branch is one of Toyota dealers in Pekanbaru is located at Jl. Sutomo 13 Pekanbaru. PT Agung Automall Sutomo Pekanbaru branch charged with marketing activities for the products produced. Marketing includes the company's business that starts with identifying consumers' needs should be satisfied, determine the products to be manufactured, determine appropriate product prices, determine ways of promotion and distribution / sale of such products, and eventually the resulting product is up to the consumer.The data used are primary data and secondary data. Sub variables studied consisted of positioning against Attributes, benefits, competitors, price, usability. The analysis used is descriptive analysis. Sampling was conducted in stages with accidental sampling method with a total sample of 76 respondents.The Results of research and testing of consumer products hepotesis author of the Toyota Avanza in PT. Agung Automall Pekanbaru showed that five variables positioning above the most dominant factor in influencing consumers to buy products at PT Toyota Avanza. Agung Automall is based on the usability of the product. Respondents tend to be more familiar with the product Toyota Avanza due to the usability of the product is a versatile car, so positioning is done can be said to be successful, while the lowest dimension is positioning according to price, it means the product Toyota Avanza has a fairly high price compared with the price of other products are now increasingly cheap.Keywords: Positioning, Strategy, Implementation